Designing of a solar panel deployment mechanism for small satellite - Kabir, Saqib (Department of Electrical Engineering, 2021)
In the last few years, there has been a considerable increase of low cost space mission. Almost every small satellite has appendages like Solar Panels OR Antennas. These appendages have large inertial forces with low structural rigidity and mass to size ratio. These appendages are in stowed position in launcher to accommodate the whole satellite in the Launcher. However after launching these appendages are deployed to obtain the required power and the pointing of antennas. Their power producing capability is directly related to their area of exposure to sun, that is why these panels are available in different sizes and configurations. The requirement for the deployment mechanism for these appendages need to be cost effective, compact, lighter in weight and simple. It is entirely dependent on the structural designer to create such a robust mechanism that conforms to the requirements of the mission. In order to deploy the solar panels, it is mandatory that some sort of actuating system is employed. In this regard, we are aiming to use the torsional spring to induce the required torque for the deployment. There has been a considerable amount of research work [1-4] for a robust deployment mechanism to deploy the solar panel reliably without compromising on the overall cost and strength of the system. To realize the practical utility of Torsion Springs [5] for solar panel deployment, with the deficiency of locking after deployment and hold down mechanism when stowed. We propose a simple actuation scheme of designing the mechanism using Spiral Torsional spring for small satellite with its Zero 'g' testing and mitigation of expected Risks.